1975
DOI: 10.1143/jjap.14.779
|View full text |Cite
|
Sign up to set email alerts
|

ESR and Electric Conductance Studies of the Fine-Powdered SnO2

Abstract: A fine-powdered sample of high purity SnO2 gave a strong ESR signal (gav≈1.90) after reduction in vacuum. This BSR center, like the g≈1.96 center of ZnO, is associated with the n-type conduction. When the sample was exposed to O2 or H2, the spin concentration, the full half width and also the electric conductance were changed. These variations are well explained by assuming that the fine-powdered SnO2 has double donor centers originated from both bulk and surface oxygen vacancies, The gav≈1.90 center may be du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 0 publications
1
25
1
2
Order By: Relevance
“…We conclude that H O is stable enough to explain the observed unintentional n-type conductivity in SnO 2 [5,8]. Indeed, an increase in carrier concentration has been observed upon exposure to moist air or H 2 [12,13]. Nola et al [13] also reported a decrease in the number of donors upon annealing at 573 K, consistent with our calculated barrier of 2:2 eV for the motion of H O .…”
Section: Prl 101 055502 (2008) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 89%
“…We conclude that H O is stable enough to explain the observed unintentional n-type conductivity in SnO 2 [5,8]. Indeed, an increase in carrier concentration has been observed upon exposure to moist air or H 2 [12,13]. Nola et al [13] also reported a decrease in the number of donors upon annealing at 573 K, consistent with our calculated barrier of 2:2 eV for the motion of H O .…”
Section: Prl 101 055502 (2008) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 89%
“…If, instead, this level can be attributed to V O , which becomes more dominant once the hydrogen donors are removed, then our calculated value is also in good agreement with this result. We note that a level at 0.28-0.35 eV has been observed in many n-type samples [75,[164][165][166] (as has the ∼0.15 eV level) [73][74][75]167], and that, in a study on SnO 2 nanoparticles [168], a switching of activation energy from 0.11 to 0.35 eV was observed in the largest nanoparticle when changing from low to high temperature.…”
Section: Sn Omentioning
confidence: 51%
“…A clear increase in conductivity as P O 2 is decreased can be observed when temperature T > 1000 K, indicating the presence of a relatively deep donor [34]. From these data, a donor activation energy of 0.15 eV in the dilute limit has been derived [72][73][74], or possibly at ∼0.3 eV [75], but the majority of computational studies indicates that the most likely donor, the oxygen vacancy, is deeper with the (2+/0) transition occurring at about 1 eV below the conduction band minimum (CBM) [20,41,43].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…According to electro-physical study data, ionized oxygen vacancies in tin dioxide form shallow donor levels with an energy of ~0.03 and ~0.15eV below the bottom of the CBM [9,10,11]. In electron spin resonance measurements, other authors have observed the existence of donor levels from ~0.15eV up to ~0.30eV underneath the CBM [12]. Note that the literature only shows how, for a given 4 sample, one (or several) discreet levels are placed around this 0.15eV broad energy region but does not suggest the existence of a continuous band 0.15eV wide.…”
Section: -Results and Discussionmentioning
confidence: 99%